Occupational stress and fatigue as risk factors for hypertension among employees at PT. Perkebunan Milano, Kebun Sei Daun - Eva Ellya Sibagariang; Jesika Meyanti Saragih; Kartika Sari Rizki; Rosmeri Br Bukit; Disti Amanda Putri; Mafe Robbi Simanjuntak; Roslenni Sitepu; Nindia Putri (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Hypertension is a major public health problem with increasing prevalence and is a primary risk factor for various cardiovascular diseases. Workers exposed to work stress and work fatigue are at higher risk. This study aimed to determine the relationship between work stress and work fatigue with the incidence of hypertension among employees at PT. Milano Kebun Sei Daun.  Method: This quantitative study used a cross-sectional design. The population comprised all 52 employees, and total sampling was used to include all as respondents. Data were collected using questionnaires, observation sheets, and blood pressure measurements. Univariate analysis described frequency distributions, and bivariate analysis used the chi-square test (α=0.05). Results: The study found that 14 respondents (26.9%) had hypertension. Among those with high work stress, 2 had hypertension; among those with high work fatigue, 3 had hypertension. Chi-square tests showed significant associations between work stress and hypertension (p=0.044) and between work fatigue and hypertension (p<0.001). Conclusion: There are significant relationships between work stress and work fatigue with the incidence of hypertension among employees at PT. Milano Kebun Sei Daun. Workplace interventions to reduce stress and fatigue are recommended.